A viroporin-like 2B protein of duck hepatitis A virus 1 that induces incomplete autophagy in DEF cells - Zezheng Liu (Poultry Science, 2021)
ABSTRACT: Duck hepatitis A virus 1 (DHAV-1) can cause high morbidity and fatal acute infectious hepatitis in ducklings, which seriously endangers animal husbandry. Viroporin is a small molecular weight hydrophobic transmembrane protein encoded by the virus, that has been suggested to induce autophagy in host cells by increasing the membrane permeability through disturbing the ion balance. In this study, we aimed to investigate whether the DHAV-1 2B protein can induce autophagy in DEF cells with a viroporin-like function. Bioinformatics analysis has indicated that the 2B protein is characterized by a viroporin domain, which is consistent with the type IA viroporin transmembrane protein. We experimentally confirmed that the 2B protein disturbed the Ca2+ balance of infected cells by elevating the intracellular Ca2+ concentration. Eukaryotic expression of the 2B protein upregulates the expression of microtubule-associated protein 1 light chain 3 II (LC3-II) and the number of autophagosomes in the cell. Interestingly, the Western Blot (WB) results showed that 2B protein expression induced less protein degradation of the autophagic substrate sequestosome 1 (SQSTM1/p62) than the positive control, while microscopy observations showed that the autophagosomes did not colocalize with the lysosomes. In summary, 2B protein expression induced autophagy in host cells, but the autophagic flow was incomplete. The results of this experiment are expected to provide reference scientific data for elucidating the infective and pathogenic mechanism of DHAV-1.